Genetics of drug‐induced liver injury: Current knowledge and future prospects - Ann K. Daly (Wiley, 2023)
Abstract Idiosyncratic drug‐induced liver injury (DILI) remains an important clinical problem, both during drug development and the prescription of a range of licensed drugs. Although rare, the consequences are serious. Ongoing studies on genetic risk factors for DILI, especially genomewide association studies, have resulted in the identification of a number of genetic risk factors, including particular HLA alleles and a few non‐HLA genes, both immune‐related and metabolic. Some non‐HLA associations, such as N‐acetyltransferase 2 in isoniazid DILI and interferon regulatory factor 6 in interferon‐beta DILI are likely to be drug‐specific due to the role of the associated gene, but there is also evidence for polygenic susceptibility involving pathways such as oxidative and endoplasmic reticulum stress and mitochondrial function for DILI induced by multiple drugs. Increased knowledge of genetic risk factors should assist in better understanding underlying DILI mechanisms and help improve methods for identifying hepatotoxic drugs early in development. HLA allele‐specific T cell proliferation together with in silico prediction of drug binding to specific HLA proteins have confirmed genetic findings for certain common causes of DILI. However, studies in hepatocytes exposed to high drug concentrations suggest toxicity that is not dependent on genotype also occurs. It seems likely that susceptibility to DILI involves several genetic risk factors combining with other factors that affect drug levels. Despite recent progress in detecting genetic risk factors for DILI, low positive predictive values mean that general implementation of genotyping prior to prescription of potentially hepatotoxic drugs is not useful currently.